Inside Back Cover: Microarray Analysis of Antibodies Induced with Synthetic Antitumor Vaccines: Specificity against Diverse Mucin Core Structures (Chem. Eur. J. 16/2017). Issue 16 (27th January 2017) - Pett, Christian; Cai, Hui; Liu, Jia; Palitzsch, Björn; Schorlemer, Manuel; Hartmann, Sebastian; Stergiou, Natascha; Lu, Mengji; Kunz, Horst; Schmitt, Edgar; Westerlind, Ulrika
Abstract : To evaluate antibodies directed against tumor‐associated MUC1 glycoproteins, a library was prepared consisting of mucin glycopeptides, ranging from small tumor‐associated glycans to elongated O‐glycan core structures. Microarray profiling showed that the induced antibody response was characteristically different for antibodies directed to the immune‐dominant PDTR or GSTA glycosylation sites of MUC1. All antisera showed high reactivity to the tumor‐associated saccharide structures on MUC1. Extensive glycosylation with branched core 2 structures, typically found on healthy cells, abolished antibody recognition of the antisera and suggest that all vaccine conjugates preferentially induced tumor‐specific immune responses. More information can be found in the Full Paper by U. Westerlind et al. onpage 3875 ff.